(untitled) (Eurasian Research Bulletin, 2022)
The article is devoted to the actual problem of corrosion of oilfield equipment and effective methods of dealing with it.The authors of the article faced the real problems of one of the largest oil fields in the Republic of Uzbekistan.The application of a set of measures for corrosion protection, comprehensive monitoring of the corrosion situation, the use of modern solutions, including the development of proprietary chemical reagents, made it possible to significantly reduce the statistics of equipment destruction under the influence of corrosion processes, as well as to increase the level of industrial safety of the facility as a whole.